Contemporary anthropology : theory and practice - Nurul Alam, S. M.; Jāhāṅgiranagara Biśvabidyālaẏa. (Dhaka : University Press, 2002)
Contributed articles with reference to Bangladesh.
"Jahangirnagar University."
Includes bibliographical references and index.
Keywords: Anthropology -- Bangladesh; Ethnology -- Bangladesh; Bangladesh -- Social life and customs